Lysophospholipid (LPA) receptors (version 2020.5) in the IUPHAR/BPS Guide to Pharmacology Database. (2020) - Blaho, Victoria; Chun, Jerold; Jones, Danielle; Jonnalagadda, Deepa; Kihara, Yasuyuki; Moolenaar, Wouter; Ngo, Tony; Ray, Manisha; Tan, Valerie
No abstract available